Revision of Oxalis section Palmatifoliae DC. (Oxalidaceae) - López, Alicia; Panseri, Andrea F.; Urtubey, Estrella (Phytotaxa, 2013)
A taxonomic revision of Oxalis section Palmatifoliae is presented, together with cluster analyses to clarify the limits of the species. This monophyletic section includes five species endemic from Southern Argentina and Chile. A key for the species, descriptions, illustrations, synonymy, and geographical distribution for each species are also provided. Five lectotypifications and two new synonymies are proposed.